Mulching and integrated nutrient management practices on enhancing soil microclimate and productivity in rabi maize (Zea mays) under eastern Indian conditions - PRIYANKA, E; KURMI, K; PRIYADARSHINI, ARATI; PATTANAIK, SUBRAT (The Indian Journal of Agricultural Sciences, 2025)
The performance of winter (rabi) maize (Zea mays L.) is mostly constrained by low soil moisture and nutrient availability. In such cases, integrated nutrient management and moisture conservation techniques have shown promising results. The present experiment was conducted during winter (rabi) season of 2020–21 and 2021–22 at the Instructional-cum-Research Farm, Assam Agricultural University, Jorhat, Assam to assess the effect of mulching and Integrated Nutrient Management practices (INM) for enhancing soil microclimate and productivity in rabi maize. The experiment was laid out in split-plot design (SPD) in sandy loam and acidic soils consisting of three mulching treatments, viz. No mulch (M0), paddy straw mulch (M1) and biodegradable film mulch (M2) as main plots and sub-plot included eight INM treatments, viz. 100% recommended dose of fertiliser (RDF) (I1); 100% RDF + water spray (I2); 100% PK + 75% recommended dose of nitrogen (RDN) + 25% RDN through vermicompost (I3); 100% PK + 75% RDN + 25% RDN through enriched compost (I4); I3 + 4% Vermiwash (I5); I4+4% Vermiwash (I6); I3 + 4% Humic acid (I7) and I4 + 4% Humic acid (I8); and maize hybrid DKC-9081 was used in this experiment. Among all the treatments, M2 consistently performed well by enhancing soil temperature, soil moisture content, emergence count (%), LAI and yield attributing parameters like cob girth, cob length and grain yield increased by 16.57% compared to M0 and M1. Among the INM treatments, integrating nitrogen with enriched compost and foliar spray of humic acid proved effective. Results revealed that the M2 and nitogen integrated with enriched compost and humic acid (I8) which was applied through foliar spray resulted in higher growth and productivity presenting a sustainable pathway for improving yield potential under rabi maize.